Do public and private support create sustainable housing pathways for disadvantaged populations? - O'Donnell, James (My University, 2018)
This paper presents a multistate demographic approach for analysing the longitudinal dynamics of housing and homelessness. This approach is applied to a sample of highly disadvantaged individuals in Australia to assess whether private housing markets and interpersonal support networks provide stable housing trajectories vis-à-vis public and community (social) housing. Discrete-time competing risk survival models are specified to estimate the hazards of exiting housing to three housing and homeless states. Model outputs are applied to multiple decrement life tables to estimate the duration of episodes and the cumulative incidence of subsequent episodes of housing and homelessness. The results suggest that private housing markets carry an increased risk of housing exit relative to social housing. The homes of family and friends are the most common destination, though this type of support is usually time limited and often precipitates episodes of homelessness. These findings warrant policy consideration as to how housing markets can provide better affordability and security for low income households.
Keywords: Housing, communities and neighbourhoods; Housing, communities and neighbourhoods